Trouble with the Child in the Carceral State - Meiners, Erica R. (Social justice, 2014)
The article discusses the use of the concept of "the child" in the debates surrounding incarcerations, prisons, and the prison industry. Topics include racial, sexual, and gendered inequalities in who qualifies as a child; the use of the concept to justify both prison closings and prison openings; and the differences in treatment of individuals termed children, juveniles, adolescents and adults, such as imprisonment.